2005
DOI: 10.1145/1071690.1064242
|View full text |Cite
|
Sign up to set email alerts
|

End-to-end estimation of the available bandwidth variation range

Abstract: Abstract-The available bandwidth (avail-bw) of a network path is an important performance metric and its end-to-end estimation has recently received significant attention. Previous work focused on the estimation of the average avail-bw, ignoring the significant variability of this metric in different time scales. In this paper, we show how to estimate a given percentile of the avail-bw distribution at a user-specified time scale. If two estimated percentiles cover the bulk of the distribution (say 10% to 90%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…Finally, our calibration study has focused on average AB over a time interval. PATHLOAD reports a variation range for AB, and Jain et al [17,31] have shown that the variation of AB is an important measurement target. Extending our calibration study to consider AB variation is a subject for future work.…”
Section: Limitations Of Yazmentioning
confidence: 99%
“…Finally, our calibration study has focused on average AB over a time interval. PATHLOAD reports a variation range for AB, and Jain et al [17,31] have shown that the variation of AB is an important measurement target. Extending our calibration study to consider AB variation is a subject for future work.…”
Section: Limitations Of Yazmentioning
confidence: 99%
“…More recently proposed schemes, including pathload [4], [5], pathvar [9], TOPP [3], PTR/IGI [6], pathchirp [7], and BFind [8], adaptively vary the rate of probing traffic to induce congestion in the network. This has been found to increase the fidelity of estimation methods.…”
Section: Available Bandwidth Estimation Techniquesmentioning
confidence: 99%
“…The benefits of knowing how much network bandwidth is available to an application has motivated the development of techniques that infer the available bandwidth from traffic measurements [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12]. Even though the number of techniques available today is significant and much empirical experience has been gained, less progress has been made towards a foundational understanding of measurement based methods for estimating the available bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…This case is typically the hardest to estimate since a tight high-speed link implies that its utilization needs to be very large, at least 90% in all our cases. It has been shown in [10] that as the utilization of the tight link increases, so does the variation in the average available bandwidth, the metric that we are measuring. Cases 2,3, and 4 are designed to stress-test our estimation methodology in heavily loaded network paths.…”
Section: Test Casesmentioning
confidence: 99%
“…This link is referred to as the tight link. Tools to estimate the end-to-end available bandwidth of a network path, defined as the available bandwidth at the tight link, have been proposed in [7,22,9,18,19,26,14,10].…”
Section: Introductionmentioning
confidence: 99%